NOTE ON THE OCCURRENCE OF NEMIPTERUS METOPIAS (BLEEKER) FROM MADRAS COAST - Indra, T J (Indian Journal of Fisheries, 2011)
The thread-fin breams or monocle breams constitute an importantgroup of commercial fishes in India. Of the 20 species of the genus NemipterusSwanson recorded from the Indo-Australian Archipelago (Weber and Beaufort1936) only five are represented in the Madras Coast viz. N. delagoae Smith,N. japonicus (Bloch); N. nematophorus (Bleeker); N. mesoprion (Bleeker) andN. tolu (Valenciennes). N. japonicus and N. tolu occur almost throughout theyear. Whereas the other species are seasonal. The occurrence of yet anotherspecies viz. N. metopias (Bleeker) is reported by the author.